Recycling the Margins: Re-Thinking the Role of Architecture in Everyday Urban Places - Shannon Criss (Oz, 2006)
Architectural education can provide space for investigations and new lines of communication; this essay reveals the efforts of many students and myself to make sense of the role that architecture might play in everyday urban places. Through an encounter with a Kansas City, Kansas planner, my students and I became involved with a group of residents who recently had started the Boulevard Neighborhood Association.